Pariwisata Ubud dalam Teologi Hindu (Manawa Dharma Sastra) - I Wayan Miartha (PARIWISATA BUDAYA: JURNAL ILMIAH PARIWISATA AGAMA DAN BUDAYA, 2021)
Ubud is one of the destinations of a worldwide tourist destination, Ubud which originally was an agrarian traditional village turned into a tourism village, even the village of Ubud has been transformed into a world tourism destination is evidenced by the many awards obtained in the field of tourism. Ubud tourism practitioners have been able to meet the standard of facilities that become the standard needs of tourists themselves, both nationally and internationally, such as the availability of accommodation, restaurant, telecommunications, transportation, entertainment, museums, art gallery and other supporting objects close to Ubud such as Bedahulu, Pejeng, Tampaksiring etc. Ubud tourism is not the same as other tourist destinations in Bali such as Nusa Dua, Sanur, Kuta and others, because Ubud people have different characteristics and lifestyles, the management of Ubud tourism through the concept of Tri Hita Karana combined with Hindu Theology so that existence Ubud tourism can be maintained. In Veda (Manava Dharma Sastra) states that how to serve Tourists such as